Soluble programmed cell death protein 1 (sPD‐1) and the soluble programmed cell death ligands 1 and 2 (sPD‐L1 and sPD‐L2) in lymphoid malignancies. (12th April 2021) - Mortensen, Julie B.; Monrad, Ida; Enemark, Marie B.; Ludvigsen, Maja; Kamper, Peter; Bjerre, Mette; d'Amore, Francesco
Abstract: Background: The programmed cell death protein 1 (PD‐1) and its ligand 1 and 2 (PD‐L1/PD‐L2) regulate the immune system, and the checkpoint pathway can be exploited by malignant cells to evade anti‐tumor immune response. Soluble forms (sPD‐1/sPD‐L1/sPD‐L2) exist in the peripheral blood, but their biological and clinical significance is unclear. Method: Time‐resolved immunofluorometric assay (TRIFMA) and enzyme‐linked immunosorbent assay (ELISA) were used to measure sPD‐1, sPD‐L1, and sPD‐L2 levels in serum from 131 lymphoma patients and 22 healthy individuals. Results: Patients had higher sPD‐1 and sPD‐L2 levels than healthy individuals. In diffuse large B‐cell lymphoma, patients with high International Prognostic Index score had higher sPD‐1 levels and sPD‐L2 levels correlated with subtype according to cell of origin. Compared to other lymphoma types, follicular lymphoma displayed higher sPD‐1 and lower sPD‐L1 levels along with lower ligand/receptor ratios. Conclusion: This is the first study to simultaneously characterize pretherapeutic sPD‐1, sPD‐L1, and sPD‐L2 in a variety of lymphoma subtypes. The relation between higher sPD‐1 levels and adverse prognostic factors suggests a possible biological role and potential clinical usefulness of sPD‐1. Moreover, the reverse expression pattern in follicular lymphoma and T‐cell lymphoma/leukemia may reflect biological information relevant for immunotherapy targeting the PD‐1 pathway.